Mobile autothermic prototype for biochar production using biomass of avocado crop byproducts - Medina Orozco, Lenin Ejecatl; Medina Orozco, Iván N. (REVISTA TERRA LATINOAMERICANA, 2018)
The state of Michoacán, Mexico, is the world’s largest producer of avocado. The social and economic impact of this crop depends on the area under cultivation. By-products of this activity are derived from pruning for tree maintenance. Using avocado byproducts is seen as an economically, environmentally and socially viable alternative for producing biochar in large volumes, without extracting timber from forests and pristine jungles. The objective of the present study was to build a mobile autothermic biochar-pyrolysis prototype, with a useful volume of 1.7 m3 of crushed biomass and evaluate its performance in field conditions. The equipment was built of stainless steel to give it a useful life of 7 years of intensive use, with mobility within the agricultural fields. It is autothermic so as not to depend on an external heat source. The equipment was low-cost compared to commercial equipment ( 700 000.00 MN pesos) and has future potential in cogeneration of energy. The main variable in manufacturing cost is the market price of stainless steel. The equipment reported a conversion rate of biomass to biochar, under field conditions, of 300 to 400 kg per day, with an average recovery rate of 16% in biochar. The main variables in the transformation of biomass to biochar were moisture, size of chips and atmospheric conditions. A Cation Exchange Capacity (CEC) of 46 Cmolc kg‑1 and pH 10.25 were found. The equipment successfully transformed avocado biomass, and the biochar had suitable characteristics for volcanic soils.